A Systemic Investigation on the Sensing Behaviors for Dopamine Based on the Combination of Cu-MOF and Various Carbon Materials. Issue 4 (1st April 2023) - Zhang, Jing; Liu, Lu; Zhuang, Xiaoli; Meng, Wei; Ren, Dongmei; Wang, Yue; Tong, Boran; Han, Chao
Abstract : Two-phase composites of Cu-MOF/X (X = multi-walled carbon nanotube (MWNT), graphene, poly (3, 4-ethylenedioxythiophene) (PEDOT), acetylene black (AB)) were constructed and used as electrode materials for dopamine (DA) sensing in this work, respectively. The sensing performances of these modified electrode based on different carbon materials were systematically investigated. The DPV analysis data showed that compared with naked GCE and Cu-MOF/GCE, Cu-MOF/X/GCE (X = MWNT, graphene, PEDOT, AB) showed good electrocatalytic activity and DA oxidation sensing behavior because of the good conductivity of carbon materials. Moreover, the systematical investigation of sensing performances based on each modified electrode showed that: on the one hand, the sensing behaviors of each modified electrode were greatly influenced by the content of carbon material; on this other hand, the modified electrode based on different carbon material all exhibited different sensing behaviors. Cu-MOF/MWNT/GCE showed the best performance in the range of DA concentration from 0.5 to 200 μ M, and the maximum sensitivity was 0.252 μ A· μ m −1 . In addition, the selectivity, reproducibility and stability of Cu-MOF/X/GCE (X = MWNT, graphene, PEDOT, AB) were all carried out.